Textbooks and digital resources: current transformations in France - Magali Loffreda; Xavier Levoin; Éric Bruillard (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2017)
Many discourses emphasize the great educational potential of digital technologies. These technologies can renew both the activities carried out with students, the management of their learning paths, working methods, etc. In theory, this will be beneficial for education. But the evolution of these technologies in the field of education does not necessarily lead to idyllic results. In reality, the changes observed in these areas are slow and are based on very localized, rarely convergent, and often incomplete. Several elements are likely to determine the uses of computer technologies: the strategies of publishers and links with «EdTech» companies; political choices (in terms of curricula, equipment, examinations, etc.); materials (tablets, smartphones, etc.); educational resources, their modes of production and exchange, the place of free educational resources; changes in national and European legislation about digital matters. In this paper, we will try to show how the French publishing landscape and access to educational resources is currently undergoing important changes, starting from a configuration where textbooks are central to sketch out the current situation, where the supply of online digital resources seems to open up alternatives. We will rely in particular on the case of a portal of resources financed by the Ministry of National Education and published by consortia bringing together publishers and EdTech structures.